A novel active building envelope with reversed heat flow control through coupled solar photovoltaic-thermoelectric-battery systems. (15th August 2022) - Luo, Yongqiang; Cui, De'en; Cheng, Nan; Zhang, Shicong; Su, Xiaosong; Chen, Xi; Tian, Zhiyong; Deng, Jie; Fan, Jianhua
Abstract: Heat transmit between ambient and indoor space passively through building envelope. This heat flow intensity can be reduced by using insulations and eliminated by conventional air conditioner, which causes huge amount of energy. In this study, a new concept is proposed for a new active building envelope system that can realize heat gain/loss control and in some senses the conventional air conditioner system could be saved, because it is shown that the building envelope itself could be an air conditioner. It should be specially noted that, we can set parameter Q w in this system to determine how much extra thermal energy you want from the new building envelope. It is based on the combination of photovoltaic (PV), thermoelectric modules (TEM), energy storage and control algorithms. Five types of systems, namely PV + TE (S1), Grid + TE (S2), PV + Grid + TE (S3), PV + Battery + TE (S4) and PV + Grid + Battery + TE (S5) are studied. It is found that in all the five systems, there is a typical optimum setting of thermal load for each one of them with minimum annual power consumption. Graphical abstract: Image 1 Highlights: A new concept of building envelope can achieve reversed heat flow. Energy flow control model is established for realizing the concept. Energy analysis is performed for five types of systems under the framework. The join of battery can enhance performance and reduce power abandon.